2019
DOI: 10.3389/fpls.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

The Altered Expression of microRNA408 Influences the Arabidopsis Response to Iron Deficiency

Abstract: MicroRNAs contribute to the adaptation of plants to varying environmental conditions by affecting systemic mineral nutrient homeostasis. Copper and iron deficiencies antagonistically control the expression of Arabidopsis thaliana microRNA408 ( miR408 ), which post-transcriptionally regulates laccase-like multicopper oxidase family members LAC3 , LAC12 , and LAC13 . In this work, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 74 publications
(131 reference statements)
2
28
0
Order By: Relevance
“…Consistent with this idea are the observations reported in several plant species where miR408 expression causes higher chloroplast Cu content and improved photosynthesis, growth, and seed yield in diverse plant species [42,44,45]. On the other hand, Carrió-Seguí et al have reported that both overexpression and loss of miR408 caused a diminished plant performance, especially in low Fe conditions [46].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with this idea are the observations reported in several plant species where miR408 expression causes higher chloroplast Cu content and improved photosynthesis, growth, and seed yield in diverse plant species [42,44,45]. On the other hand, Carrió-Seguí et al have reported that both overexpression and loss of miR408 caused a diminished plant performance, especially in low Fe conditions [46].…”
Section: Discussionsupporting
confidence: 67%
“…Besides Cu availability, other environmental conditions have been reported to affect Cu-microRNA expression [27]. This was convincingly shown in Arabidopsis for cold [47,48,49], Fe availability [46,50], or stresses that are predicted to induce reactive oxygen species accumulation such as high light, the herbicide methyl-viologen, and excessive toxic metal [29]. In our setup, we controlled growth conditions and attempted to avoid any additional stressors.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the relationship between miRNA biosynthesis and the cellular energy status is also supported by the fact that the transient overexpression of the energysensing SnRK1 in protoplasts leads to the repression of a variety of miRNAs (Confraria et al, 2013). These include miRNA159B (involved in leaf senescence, Huo et al, 2015), miRNA161 (induces the expression of PPR genes, Cai et al, 2018), miRNA775A (no function reported to date), and miRNA824A (involved in flowering time regulation, Hu et al, 2014) and might be involved in SnRK1-dependent energy signaling. However, the molecular regulatory network involved in this SnRK1-dependent miRNA biosynthesis remains an open question.…”
Section: Sugars and Micrornasmentioning
confidence: 99%
“…The miRNA398 binding site of CSD1 can be eliminated by alternative splicing in peanut and Arabidopsis, resulting in different tolerance levels to abiotic stress (Park and Grabau, 2017), indicating how alternative splicing processes influence plant response through interactions with miRNAs. Microarray analyses have also shown responsiveness to sucrose from other mature miRNAs in Arabidopsis (Figure 2), including miRNA408 (involved in the response to iron deficiency and in photosynthesis; Pan et al, 2018;Carrió-Seguí et al, 2019), miRNA319 (involved in leaf development; Koyama et al, 2017), and miRNA160 (involved in heat tolerance; Lin et al, 2018). The levels of miRNA319 and miRNA408 are enhanced by sucrose supply, while the levels of miRNA160 are reduced.…”
Section: Sugars and Micrornasmentioning
confidence: 99%
“…In this context, the characterization of multiple knockout mutants has led to the identification of the role of laccases in the lignification of Arabidopsis thaliana . Due to their important role in lignin formation, laccase and laccase‐specific microRNA genes have been recently identified as interesting targets to modulate lignin content or composition in lignocellulosic biomass . However, in spite of the increase number of scientific publications, the mechanisms regulating the spatio‐temporal patterning of lignin polymerization still remain unclear …”
Section: Interesting Roles In Naturementioning
confidence: 99%